SYSTEMATIC REVIEW: COMPARISON OF CUCUMBER JUICE WITH TOMATO JUICE IN THE EFFECTIVENESS OF BLOOD PRESSURE REDUCTION IN PATIENTS WITH HYPERTENSION - Muhammad Raihan Adiguna; Ahmad Purnama Hudaya; Ria Inriyana (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Hypertension is a disease characterized by elevated systolic and diastolic blood pressure, or the use of antihypertensive drugs. Hypertension has complications in the form of diseases that target organs including the brain, kidneys, peripheral blood vessels, and heart. This requires effective management by considering effective management in the long term. Pharmacological management of hypertension has side effects of drug-related problems (DRPs) that have an undesirable impact. This makes non-pharmacological interventions recommended for effectiveness. The utilization of fruits is part of non-pharmacological interventions, one of them is with cucumber and tomato which are processed into juice. This research aims to identify further studies through systematic review research on the comparison of the effectiveness of cucumber juice with tomato juice on blood pressure in patients with hypertension. The method used was a systematic review by identification and evaluation of literature with a quasi-experiment research design in according to predetermined eligibility criteria. Databases used included Cochrane Library, DOAJ, Google Scholar, PubMed, Science Direct, and Semantic Scholar. All relevant articles were quality assessed using JBI Critical appraisal. The results of the study resulted in 11 articles that were relevant to the criteria that had been set. The articles retrieved had a low risk of bias after quality assessment. 11 articles resulted in the finding that cucumber juice and tomato juice have ingredients that have an impact on blood pressure in hypertensive patients. Both therapies have effectiveness as hypertension management